Palm Plantation Conflict (study of Sintang Regency, West Kalimantan) - Hasan Almutahar (Proyeksi: Jurnal Ilmu-Ilmu Sosial dan Humaniora, 2017)
Conflict dynamics of oil palm plantation development was conducted in Sintang. This study used descriptive and qualitative approach. The findings are that there are still many farmers who object to the location of their plasma plantation, compared to their residence location, specified by palm plantation companies. The company seems to deliberately delay the conversion for a variety of reasons which is basically detrimental to farmers. Such a long time for conversion means that their credit responsibilities will also increase, longer than the predetermined time, seven years. Work grouping system and lending to small holder plasma farmers; the system of granting credit to farmers in group while the payment is done individually means that the diligently working farmers will feel encumbered by member shaving credit. Such a system must be improved by adding the approval not only from the cooperatives, but also from the chairman and members of the group.Keywords: conflict, oil palm, plantations